MASA DEPAN PRODI VOKASI KEUANGAN DAN PERBANKAN DI ERA NEO BANK DAN MERDEKA BELAJAR - Teddy Richendi; Slamet Soesanto (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2021)
Vocational education is education that emphasizes the importance of the profile of its graduates having certain skills that are specifically designed to meet the needs of industry as workers or as entrepreneurs. The massive use of information technology in the financial and banking industries has made it easier for people to transact business. The process of financial transactions involving a lot of human intervention can now be replaced by machines (technology). So it becomes a necessity that cannot be avoided by the banking finance study program so that it immediately adapts, where the graduate profile is prepared to be compatible with the needs of the industry. In the context of "free learning" students are given the option to explore their inner talents and abilities through learning opportunities outside the study program or outside the campus without being hampered by the completion of the main study program taken. Learning outcomes become the guide for the ongoing teaching and learning process. The driving elements for the realization of learning outcomes are: curriculum, lecturers, students, infrastructure/technology. By reconstructing the curriculum of the banking finance study program, it is hoped that this study program will be of higher quality and demand, which will then be able to have a direct positive impact on the progress of the finance and banking industry and the sustainability of the study program itself.